Заметки о дантовских подтекстах и параллелях в русской литературе первой половины XX века [Some Notes on Datean Quotations and Allusions in Russian Literature of the First Half of the 20th Century] - Levinton, Georgy (Slavica Revalensia, 2021)
This is the initial part of a larger project consisting of several separate papers. This particular paper has two parts. 1. “No Crumbs on the Table-Cloth” (a line of Pasternak’s poem) claims that a crumb motive in an early version of the poem by Boris Pasternak “Piry” (1913) reflects the initial paragraph of Dante’s Convivio with its bread metaphor (Conv. I.i.7, 10–11). Some other examples of similar echoes are quoted. 2. “The Motherland’s Shoulders” discusses the metaphor shoulders of a mountain, which can be found in a couplet by Koncheyev—a fictional poet from Vladimir Nabokov’s Dar (The Gift, 1936—37 / 1952). This metaphor was previously treated as a quote from Mandelstam’s poem “Zverinets” (1915), but here both cases (and, probably, some additional examples) are seen to go back to the same metaphor in Inf. I, 16 (where it means summit rather than mountainside) and numerous translations of Inferno into English.